Detecting fraudulent financial reporting using the fraud hexagon model: Evidence from the banking sector in Indonesia - Tarmizi Achmad; Imam Ghozali; Monica Rahardian Ary Helmina; Dian Indriana Hapsari; Imang Dapit Pamungkas (Economies, 2023)
The purpose of this study was to examine the potential for fraudulent financial reporting using the fraud hexagon theory factors such as stimulus (financial target, financial stability, and external pressure), capability (change in director), collusion (total board of commissioners who have multiple positions), opportunity (ineffective monitoring), rationalization (auditor switching), and arrogance (frequency of the number of photos of the chief executive officer (CEO) in the annual financial statements) affect fraudulent financial reporting. The sample of this study comprises banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021, with a total sample of 215 and data processing using SPSS 25 software. The results of this study indicate that external pressure and arrogance affect fraudulent financial reporting. However, financial targets, financial stability, ineffective monitoring, auditor switching, change in director, and collusion do not affect fraudulent financial reporting. Therefore, for a company to have a system for preventing the occurrence of embezzlement, the company has to create a system of detection, monitoring, and systems review policies in the field of human resources (HR).
Keywords: G32; M14; M48; 330; collusion; fraud hexagon; fraudulent financial reporting